2023
DOI: 10.3389/fped.2023.1082558
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequality in overweight/obesity among US children: NHANES 2001 to 2018

Abstract: BackgroundPrevious research has found that the prevalence of childhood overweight/obesity varies depending on household income, ethnicity, and sex. The goal of our research is to examine changes over time in socioeconomic inequality and the prevalence of overweight/obesity among American children under five by sex and ethnicity.MethodsThis cross-sectional analysis used data from the National Health and Nutrition Examination Surveys (NHANES) collected from 2001–02 to 2017–18. Overweight/obesity in children unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…In mid-low income countries like Iran, it was reported that CIs of obesity in childhood were between 0.03 and 0.10 [ 30 , 31 ]. In the Europe and US, however, the socioeconomic status was often found to be inversely associated with child and adolescent obesity [ 32 34 ], and the similar relationship was observed among adult women, except for adult men [ 35 , 36 ]. Raftopoulou and Trasfi combined CI and Foster-Greer-Thorbecke index to estimate the inequality in obesity beyond the obesity threshold and found that inequalities in depth and severity of obesity were much greater for the poor compared to the rich in Spain [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In mid-low income countries like Iran, it was reported that CIs of obesity in childhood were between 0.03 and 0.10 [ 30 , 31 ]. In the Europe and US, however, the socioeconomic status was often found to be inversely associated with child and adolescent obesity [ 32 34 ], and the similar relationship was observed among adult women, except for adult men [ 35 , 36 ]. Raftopoulou and Trasfi combined CI and Foster-Greer-Thorbecke index to estimate the inequality in obesity beyond the obesity threshold and found that inequalities in depth and severity of obesity were much greater for the poor compared to the rich in Spain [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the incidence and prevalence of obesity in childhood and adolescence is unequal, represented by a higher risk for obesity in socioeconomically disadvantaged children and adolescents. [99][100][101] Furthermore, there are social disparities in obesity management even though the evidence base is weak. 102 It is therefore imperative that drug intervention is only considered as part of a suite of options addressing obesity as a complex and chronic disease with effective comorbidity management and careful adverse event monitoring that is underpinned by a person-centred care approach, delivering healthcare with dignity and respect.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the incidence and prevalence of obesity in childhood and adolescence is unequal, represented by a higher risk for obesity in socioeconomically disadvantaged children and adolescents 99–101 . Furthermore, there are social disparities in obesity management even though the evidence base is weak 102 .…”
Section: Discussionmentioning
confidence: 99%
“…6 However, these tendencies should be interpreted cautiously as the overall trends may mask important differences by socioeconomic status and ethnicity as seen in Denmark and elsewhere. [26][27][28] Across the study period, the shape of the BMI distribution changed and became more right-skewed, whereas the median and the lower parts of the BMI distribution remained relatively constant.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta‐analysis of European children aged 2–13 years found that in most European countries, the prevalence of overweight and obesity has stabilised from 1999 to 2016 6 . However, these tendencies should be interpreted cautiously as the overall trends may mask important differences by socioeconomic status and ethnicity as seen in Denmark and elsewhere 26–28 …”
Section: Discussionmentioning
confidence: 99%